Outcome after Robotic-Assisted Thymectomy in Children and Adolescents with Acetylcholine Receptor Antibody-Positive Juvenile Myasthenia Gravis - Della Marina, Adela; Kölbel, Heike; Müllers, Maximilian; Kaiser, Olaf; Ismail, Mahmoud; Swierzy, Marc; Rueckert, Jens-Carsten; Schara, Ulrike (Neuropediatrics, 2017)
The aim of our study was to describe the long-term outcomes after robotic-assisted thymectomy in a cohort of acetylcholine receptor (AChR)-antibody (Ab)–positive, generalized juvenile myasthenia gravis (JMG). We retrospectively analyzed a cohort of 18 patients (15 females and 3 males) who underwent robotic-assisted thymectomy. At the time of diagnosis, 12/18 patients were prepubertal; the mean age was 9.8 years at the onset of the disease. All patients received therapy with pyridostigmine; additional immunotherapy included: corticosteroid therapy in 18/18, azathioprine in 14/18 patients, mycophenolate mofetil in 4/18, and cyclosporine in 1/18 patients. Eight patients received intravenous immunoglobulin and four plasma exchange. The mean age of patients at thymectomy was 11.7 years (range: 4.2–16 years). The mean duration of postoperative stay was 2.9 days. Thymectomy was followed by gradual clinical improvement (39% patients achieved clinical remission) and dose reduction in steroid therapy in all patients during the follow-up period (mean: 27.4 months). In children and adolescents with AChR-Ab–positive JMG, thymectomy has a beneficial effect on the weaning off immunosuppressive therapy in patients with generalized symptoms and should be considered as a part of multimodal therapy. Robotic-assisted thymectomy is a safe procedure with low morbidity and a comparable clinical outcome compared with the open sternal procedure.
Keywords: juvenile myasthenia gravis; acetylcholine receptor antibody; robotic-assisted thymectomy; outcome